Levamisole in treatment of urethane-induced pulmonary carcinoma in rats - Luiz Costa e Silva, André; Medeiros Soares Celani, Livia; Medeiros Azevedo, Italo; Cunha Medeiros, Aldo (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2019)
Objective: The potential antitumor effects of the levamisole immunomodulatory agent remain uncertain, and its beneficial effects with increased survival in the adjuvant treatment of malignant tumors are controversial. The present study aims to compare the effects of levamisole with cisplatin in the treatment of urethane-induced lung carcinoma in rats. Methods: Wistar rats were allocated into three groups (n = six each). Group A: mice with lung tumor + treatment with levamisole. Group B: mice with lung tumor + cisplatin treatment. Group C: mice with lung tumor + saline treatment. After 12 weeks of the tumor induction process, the results were validated by ex vivo fluorescence imaging, determining the mean fluorescent intensity in the animal’s lungs. Serum dosages of cytokines and alkaline phosphatase were performed. Results: Mean fluorescence intensity (MFI) in the lungs (ex vivo) was measured in all animals subjected to urethane effects. In levamisole-treated, the intensity (245 +/- 15) was lower than in cisplatin-treated (277 +/- 28), but the difference was not statistically significant (p<0.05). In those treated with saline, the MFI was 680 +/- 57, significantly higher than in the other groups (p<0.05). Dosages of TNF-? (pg/ml), IL-I? (pg/ml), IL-6 (pg/ml) and alkaline phosphatase (mg/dl) were significantly lower in levamisole-treated rats than in rats with cisplatin and saline (p<0.005). Conclusion: In conclusion, this study demonstrates the positive influence of levamisole in treatment of urethane-induced lung tumors in rats.